Diversidade cultural, morfológica e patogênica de isolados de Lasiodiplodia theobromae associados a frutíferas tropicais. - Lima, Joilson Silva (2011)
Lasiodiplodia theobromae is an ubiquitous, polyphagous and opportunistic fungus with a reduced pathogenic ability. Nevertheless, it may infect several plant species over tropical and temperate regions, causing many different kinds of symptoms. The increasingly expansion of diseases caused by L. theobromae in tropical fruit plants has been imposing severe losses both at orchard level and in post-harvest at market, threaten the fruit crop industry in Northeast Region of Brazil. Therefore there is an urgent need for research pursuing basic knowledge on population biology of the fungus and host-pathogen interactions. This study aimed to characterize a L. theobromae population which has been associated to tropical plant species growing under different ecosystems in northeastern Brazil. Colony growth in culture, color and size of conidia and ability to cause disease upon inoculation on cashew nut (Anacardium occidentale), soursop (Annona muricata), yellow mombin (Spondias mombin) and Brazil plum (Spondias tuberosa) were evaluated. He study was carried out at Plant Pathology Lab and screenhouse of Embrapa Agroindustria Tropical in Fortaleza, Ceará State. Results showed a high diversity of morphology and hyphal growth among fungus isolates. Also, a very high variability on disease expression upon inoculation into four plant species was observed. However, it was found a lack of specificity of isolates as to infect cashew plants, since all isolates were able to infect cashew with similar high aggressiveness, which demonstrated a high degree of susceptibility of cashew clone used (CCP 76). Similar results were found also for soursop plants as host. Brazil plum showed a very high resistance to all isolates. The data points out for the existence of morphological and pathogenic interactions within L. theobromae population studied. According with the results, altitude and region of isolate origin has no effect on the studied features.